PERANAN AMWCHR DALAM UPAYA PENURUNAN ANGKA PERNIKAHAN ANAK DAN PAKSA DALAM KOMUNITAS MUSLIM DI AUSTRALIA - Hani Fatunnisa; Badrus Sholeh (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
Abstract: The whole world has recognized that child marriage and forced marriage (CFM) are acts that are contrary to human rights and are considered to be gender-based violence. The Australian Government since 2013 through its constitution has criminalized acts of child and forced marriage so that the perpetrators can be subject to criminal penalties. However, this policy did not effectively reduce the effect on CFM cases in Australia. It is proven that from 2017 to 2019 there was an increase in the number of victims of forced marriage and children who were categorized as victims of human trafficking in Australia. The criminal law in the CFM case is considered ineffective because the protective impact is not sustainable. The high rate of forced marriage among Muslim women in Australia is driven by high gender inequality, migration and harmful traditional cultural practices. The Australian Muslim Women's Center for Human Rights (AMWCHR) is a Muslim women's organization that seeks to advance the rights and status of Muslim women in Australia. AMWCHR has multicultural and hybridity characteristics that are not tied to any Islamic sect. This article aims to analyze the role of the AMWCHR in efforts to reduce the rate of child, early and forced marriage for Muslim women, especially in the Australian region with sustainable protection and prevention programs, based on gender equality and the principle of multi-culturalism. Keywords: Australian Government, AMWCHR, Child Early and Forced Marriage, Australian Muslim.